Batch adsorption technique for the removal of Reactive Black 5 dye from industrial waste water by using rice husks as adsorbent - Ahmed Mohammed, Asst. Lec. Luma (Al-Qadisiyah Journal of Pure Science, 2017)
The aim of this work is to absorb the Reactive Black 5 of dye with a low cost adsorbent . dye which comes in the effluents of textile industries during dyeing and rinsing processes. Although commercial activated carbon is a preferred sorbent for colour removal, its wide spread use is restricted due to high cost. Currently, the study of activated rice husks carbon as a low cost sorbent for removing dye has drawn attention of various researchers working in this field. In the present work, rice husks carbon (RHC) in the form of powder was investigated for removing dyes taking Reactive Black 5 as a model system. The adsorbent was made from pistachio shells procured from Central Iraq and was investigated under variable system parameters such as dose of adsorbent, pH , initial dye concentration , particle size and agitation time. An amount of 1.5 g/l of (RHC) could remove 95.48 % of the dye from an aqueous solution of 50 ppm with the agitation time 80 min and pH of the solution was one . The well Known Langmuir and Freundlich isotherm models were applied for the equilibrium adsorption data and the various isotherm parameters were evaluated . The results indicate that activated rice husks could be employed as a low cost alternative to commercial activated carbon in wastewater treatment for the removal of color and dyes